Two tales: the sons of adam, travels of ibrahim - Khan, Saniyasnain (GoodwordKidz New Delhi, 2004)
The first tale explores the story of Adam's sons, illustrating themes of rivalry and moral lessons. The second tale follows Ibrahim (Abraham) on his journeys, emphasizing faith, sacrifice, and dedication to God.